Measuring and Analyzing the Influence of International Trade on Economic Growth with Exchange Rate Moderation: Evidence from Selected Countries - Hakim Mhamad , Shanaz; Ali Ahmed , Younis (The Scientific Journal of Cihan University– Sulaimaniya, 2025)
This study investigates the influence of international trade on economic growth in Iraq, Turkey, Iran, and Syria from 1995 to 2023, emphasizing the moderating role of exchange rate fluctuations. Applying panel data methodologies (such as PMG-ARDL approach, and Fixed and Random Effects models), The empirical results indicate that while imports and exports have a favorable impact on economic growth over the long run, exchange rate volatility has a negative effect.. The results in turn highlight the need for infrastructure investment, exchange rate stability, and trade liberation. There are policy blueprints to further long-term economic growth too, including better governance, tapping foreign capital and fostering regional partnership.